Differential diagnosis of visceral leishmaniasis in children: a five-year retrospective study at a pediatric referral hospital - Anaisa Gomes Ramos Soares; Juliana de Sales Landim; Natiécia Gomes França; Edilson Beserra de Alencar Filho; Rodrigo Feliciano do Carmo (BMC Pediatrics)
Abstract Background Visceral leishmaniasis (VL) is a zoonotic disease caused by protozoa of the genus Leishmania and is transmitted by sandflies of the genus Lutzomyia. Children under 15 years are disproportionately affected. In pediatric patients, the clinical and laboratory features of VL often overlap with those of other infectious and hematology-oncology diseases, making differential diagnosis challenging. Rapid and accurate identification of VL is critical for effective treatment. This study aimed to evaluate the epidemiological, clinical, and laboratory characteristics of pediatric patients initially suspected of having VL and to compare their final diagnoses upon discharge from a referral hospital. Methods We retrospectively analyzed medical records of children with suspected VL, admitted between July 2014 and June 2019. Results Infectious diseases were confirmed in 61% of cases (86 patients), with VL confirmed in 55 cases. Hematology-oncology diseases were the second most common diagnosis, affecting 22.7% of patients (32 cases). Comparisons between the VL-confirmed group and those with other diagnoses revealed no significant age difference (p = 0.690). However, female sex, spleen size, and leukopenia were identified as significant predictors of VL. Conclusions Female sex, spleen size, and leukopenia were key predictors for differentiating VL from other pediatric diseases in a referral center in the Northeast Region of Brazil.